Cerebral ischemia as initial neurological manifestation of atrial myxoma: case report - Almeida Leila Azevedo de; Hueb João Carlos; Silva Marcos Augusto de Moraes; Bazan Rodrigo; Estrozi Bruna; Raffin Cesar N. (Arquivos de Neuro-Psiquiatria)
Cerebral infarctions of cardiac etiology are observed in around 20% of patients with ischemic stroke. Cerebral ischemia is the first clinical manifestation in 1/3 of cases of atrial myxomas. Although almost half of patients with atrial myxoma show changes at neurological exam, non-hemorrhagic cerebral infarction is seen in computed tomography in practically all cases. We present the case of a 40 year-old woman whose first clinical manifestation of atrial myxoma was an ischemic stroke. We point out to the possibility of silent cerebral infarction in atrial myxoma patients.